Homme et animal, la question des frontières - Camos , Valérie; Cézilly , Frank; Guenancia , Pierre; Sylvestre , Jean-Pierre (éditions Quae, 2009)
"Some arguments today lead us to question the singularity of man. From the point of view of psychological identity and cognitive performances, the difference between the great apes and man is not a question of nature but only a question of degree. Biology also considers the distinctions between man and animals as differences in nature and not differences between nature and culture. At the ethical level, animals have been instrumentalised as a result of the different ways in which we appropriate them. In addition to this, wild species are threatened today because of industrial development. Taken together, these factors lead some to consider that a true moral or legal solidarity should exist between human and animal life forms. This multidisciplinary collection addresses the entire range of these problems. Written by philosophers, ethologists, sociologists and biologists, it is intended for students and specialists in the fields addressed here and to all readers interested in this question."